THE REVIEWS OF USERS OF THE DUOLINGO APPLICATION: USABILITY AND OBJECTIVITY IN THE LEARNING PROCESS - de Araújo, Patrick Anderson Matias; Eddine, Eder Ahmad Charaf (International Journal of Research -GRANTHAALAYAH, 2020)
Since 2011, the Duolingo platform helps those who seek to learn a second language. Present in all popular mobile operating systems, it offers, in the Brazilian interface, the teaching of Spanish, French, and English language, being English the first to be made available in the platform. Given the platform’s mission of personalized teaching, making learning fun, and universally accessible, the research aims to analyze the opinions of users on the Google Play Store. The objective was to understand the usability process, ease of access, and the user-learning relationship of the application and to achieve it, it was used the assumptions of Human-Computer Interaction, that investigates the form of communication between people and computational systems, as well as forms of accessibility and facilitation of this communication. It will be used the quantitative methodology of the comments available on the digital store in the entire month of January 2020. The results show that 85.13% of the users rated the tool with the highest score, the scores range from 1 to 5, and that usability is a positive component that facilitates learning. It is noteworthy, though, that the tool can be used as an aid in foreign language teaching processes.